A Study of Multiple Deliveries in Portugal: Indications of an Iberian Peninsula Pattern. (13th August 2013) - Fuster, Vicente; Santos, Carlota; Román-Busto, Jorge; Magalhaes, Manuel
Abstract : Information on multiple deliveries with regard to Portugal is scarce. Based on data provided by the Portuguese Institute of Statistics (INE), the rates for double and triple deliveries were calculated since 1930. The results obtained show for twins a uniform temporal pattern up to the 1970s. At this time rates decreased, but later they gradually recovered, reaching their maximum level in 2010. For triplets, the highest rates occurred between 1999 and 2002. For the period 1988–2011, the rates of multiple deliveries were related to a set of variables recorded in the INE database on live births. Significant differences ( p < .001) between simple and multiple deliveries were obtained for maternal age, parity and marital status. Considering the year when the delivery occurred, significant differences ( p < .001) persisted for maternal age regardless of the year. For the type of mating, significance was consistently found since the year 2002 (either by using the marital or the cohabitation criteria), and for parity since 2003. With regard to territorial variation, throughout seven periods between 1930 and 2011, the rates among the 20 administrative Portuguese territories, including the two insular districts of Açores and Madeira, were mostly stable for twinning rates, with a minimum level in 1970–1989. Regarding triplets, the greatest inter-district variation was found after 1980. The results of the Portuguese study on multiple deliveries are interpreted in the context of the Iberian Peninsula based on findings reported for Spain.